Gaseous exchange, biochemical parameters and yield as affected by application techniques and doses of Paclobutrazol in litchi tree - Singh, Sanjay K.; Pandey, Ankit K.; Singh, Prabhakar (Indian Journal of Horticulture, 2019)
An experiment was conducted to see the effect of leaf gaseous exchange parameter, biochemical status and fruit quality of litchi cultivars China and Shahi during 2016-17 in subtropical climate of northern Bihar. Two methods of paclobutrazol (PBZ) application i.e. ring basin (RB) and trunk soil line pore (TSLP) were used with various doses of paclobutrazol (1.00-4.00 g per m canopy diameter) during September month. There was non-significant effect recorded for net photosynthetic rate during August and October but it diminishes during flowering stage (3.3 to 4.2) over control (4.96). The highest rate of transpiration was recorded during flowering phase in trees treated with 3.0 g PBZ whereas 2-3 times more stomatal conductance was recorded in PBZ applied trees @ 1 or 2.0 g through TSLP over control. During pre-FBD (i.e. October-November), leaf chlorophyll content was improved due to RB method over control. PBZ also reduced leaf Nitrogen content during October, which was conducive for flower bud differentiation in litchi trees. 4.0 g PBZ applied through TSLP method assured highest yield ((2567.66 number of fruits per tree), while in control it was only 32-140. The total sugar, vitamin ‘C’ in pulp was also recorded highest in tree treated with 4.0 g PBZ with any method of PBZ application. However same dose of PBZ with TSLP method resulted in higher Vitamin ‘C’ and total anthocyanin (28.51 mg per 100 g peel) content. Although, paclobutrazol had only small effect on gas exchange parameters but it significantly improved chlorophyll content, reduced leaf N content (just prior to FBD) and improved yield (by 10-15 fold), pulp vitamin C and anthocyaninin content.